2017
DOI: 10.1016/j.tcb.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Tribbles in the 21st Century: The Evolving Roles of Tribbles Pseudokinases in Biology and Disease

Abstract: The Tribbles (TRIB) pseudokinases control multiple aspects of eukaryotic cell biology and evolved unique features distinguishing them from all other protein kinases. The atypical pseudokinase domain retains a regulated binding platform for substrates, which are ubiquitinated by context-specific E3 ligases. This plastic configuration has also been exploited as a scaffold to support the modulation of canonical MAPK and AKT modules. In this review, we discuss the evolution of TRIBs and their roles in vertebrate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
218
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(219 citation statements)
references
References 96 publications
(135 reference statements)
1
218
0
Order By: Relevance
“…The tribbles ( trbl ) family of pseudokinases play multiple critical roles in physiology and disease (Eyers, Keeshan, & Kannan, 2016). These pseudokinases are thought to both link substrate binding to specific protein stability by recruiting ubiquitin ligases and as regulators of MAPK and AKT/FOXO - signaling (Eyers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tribbles ( trbl ) family of pseudokinases play multiple critical roles in physiology and disease (Eyers, Keeshan, & Kannan, 2016). These pseudokinases are thought to both link substrate binding to specific protein stability by recruiting ubiquitin ligases and as regulators of MAPK and AKT/FOXO - signaling (Eyers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These pseudokinases are thought to both link substrate binding to specific protein stability by recruiting ubiquitin ligases and as regulators of MAPK and AKT/FOXO - signaling (Eyers et al, 2016). There is one version of the trbl pseudokinase in Drosophila melanogaster and Caenorhabditis elegans (Kim, Thakur, Piggott, Omi, Polanowska, Jin, & Pujol, 2016; Mata, Curado, Ephrussi, & Rorth, 2000; Pujol, Cypowyj, Ziegler, Millet, Astrain, Goncharov, Jin, Chisholm, & Ewbank, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIB pseudokinases are classified based on sequence homology as serine/threonine pseudokinases that either lack (TRIB1), or exhibit low (TRIB2 and TRIB3) vestigial ATP affinity and phosphotransferase capacity (Bailey et al, 2015, Murphy et al, 2015. In addition, TRIB1 and TRIB2 are more similar (possessing a sequence homology of ~71%) compared to the most recently evolved family member TRIB3 (Eyers et al, 2017), whose homology with both TRIB1 and TRIB2 is only ~55%, suggesting mechanistic and functional divergence. Indeed earlier studies showed that when highly expressed, TRIB1 and TRIB2 but not TRIB3, degrade the myeloid transcription factor C/EBPïĄ, inhibit myeloid differentiation, and drive AML (Keeshan et al, 2006, Dedhia et al, 2010.…”
mentioning
confidence: 99%
“…TRIB3 acts as a member of tribbles homolog family that are fundamental regulators of cell cycle, differentiation, metabolism, proliferation, and cell stress, and is involved in chronic inflammatory and malignant disease through their interactions with intracellular signaling and functional proteins [4]. Our previous study revealed that TRIB3 promoted cancer development and progression by interacting with the signaling molecule SMAD3 or a selective autophagy receptor p62/SQSTM1 [5,6].…”
mentioning
confidence: 99%